Protection of a live Pasteurella multocida B:3,4 vaccine against haemorrhagic septicaemia in cattle - Adin Priadi; Lily Natalia (Jurnal Ilmu Ternak dan Veteriner, 2002)
Cross protection conferred by a live Pasteurella multocida B:3,4 vaccine to infection by P. multocida B:2, the haemorrhagis septicaemia causing bacteria in cattle was investigated. Intranasal aerogenic immunization and subcutaneous injection of the live vaccine were applied to groups I and II of 5 Bali cattle respectively. Another group (III) of 5 cattle were vaccinated with standard oli adjuvant killed vaccine intramuscularly. Cattle were observed for clinical signs and body temperatures were measured. Sera were collected monthly for 12 month and kept at -200C for further testing by ELISA. No adverse sign was observed at cattle of groups I and II after vaccination with the live vaccine. Both intranasal and subcutaneous vaccination of live vaccine showed a similar serological response which started at month-5, peaked at month-(6-7) after vaccination and still sustained at the level above positive cut-off (88 ELISA Unit) at the end of observation month-12. Cattle vaccinated with killed adjuvanted vaccine responded earlier, peaked at 5-6 month after vaccination and declined steadily till the end of investigation. At 6 and 12 months after vaccination catlle were challenged with P. multocida B:2. All vaccinated cattle challenged at 6 months (C-1) and 12 (C-2) months after vaccination survived and showed no clinical signs. Body temperatures of all vaccinated cattle were normal and ranged from 38.10C to 39.10C and 38.50C to 39.50C for cattle chalenged at C-1 and C-2 respectively. However, there was 1 cattle of group I at C-1 showed an initial increase of body temperature to 400C and decreased to normal at 42 hours after challenge. One catlle of group II had a body temperature of 40.70C detected at 5 hours post C-2 and reached a normal temperature at hour-11. Both unvaccinated cattle at C-1 and C-2 died and had body temperatures of 41.40C and 41.10C respectively at the time of death. This investigation shows that live vaccine P. multocida B:3,4 is safe and can protect cattle from haemorrhagic septicaemia for at least 12 months. This vaccine is promising to be used to replace oil adjuvanted killed bacterin for haemorrhagic secticaemia. Key words: Live aerosol vaccine, protection, haemorrhagic septicaemia, cattle